2010
DOI: 10.1016/j.foodres.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin rich fraction regulates LDLR and HMGCR gene expression in HepG2 cells

Abstract: Vanillin and its analogs have been exploited for their various health benefits. This work aimed to investigate the antioxidant properties and regulatory effects of vanillin rich fraction (VRF) extracted from vanilla pods using the supercritical fluid extraction (SFE) and commercial vanillin on low density lipoprotein receptor (LDLR) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) gene expression in HepG2 cells. The vanillin content in the VRF was 2.6% (w/w) obtained at a temperature of 80°C and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Moreover, vanillin (100 ppm) oral administration to mice resulted in detectable amounts of vanillin and its metabolites in plasma and a high antioxidant activity in the ORAC plasma assay. Recently, the ability of vanilla pod extracts (using supercritical fluids) to regulate cholesterol metabolism via upregulating the low‐density lipoprotein receptor (LDLR) gene and downregulating the 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGCR) gene in liver hepatocellular carcinoma (HepG2) cell lines was demonstrated (Al‐Naqeb and others ). In addition, Makni and others () studied the antioxidant, anti‐inflammatory, and hepatoprotective properties of vanillin in carbon‐tetrachloride‐treated rats.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Moreover, vanillin (100 ppm) oral administration to mice resulted in detectable amounts of vanillin and its metabolites in plasma and a high antioxidant activity in the ORAC plasma assay. Recently, the ability of vanilla pod extracts (using supercritical fluids) to regulate cholesterol metabolism via upregulating the low‐density lipoprotein receptor (LDLR) gene and downregulating the 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGCR) gene in liver hepatocellular carcinoma (HepG2) cell lines was demonstrated (Al‐Naqeb and others ). In addition, Makni and others () studied the antioxidant, anti‐inflammatory, and hepatoprotective properties of vanillin in carbon‐tetrachloride‐treated rats.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…Cocoa and its chocolate extract have recently been recognized as rich sources of flavonoids, mainly flavanols, which are potent antioxidant and anti-inflammatory agents with established benefits for cardiovascular health but with largely unproven effects on neurocognition and behavior ( Sokolov et al ., 2013 ). Vanilla extracts have also been reported to possess various health benefits, such as antioxidant, antimutagenic, and hypolipidemic activity, and have considerable potential as food preservatives and anticarcinogens ( Al-Naqeb et al ., 2010 ; Andrade et al ., 1992 ; Dong et al ., 2014 ; Jadhav et al ., 2009 ; Sharma et al ., 2006 ). However, most ingredients in these plant-based powders are unsuitable for use in dairy product applications due to lack of solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Chen root significantly decreased concentrations of serum TC, TG, and LDL-C and increased Ldlr mRNA in rats (Ji and Gong, 2007). Vanillin rich fraction (VRF) extracted from vanilla pods increased Ldlr mRNA in a dosedependent manner in HepG2 cells (Al-Naqeb et al, 2010). Berberine (BBR), a compound isolated from a Chinese herb, was observed to increase Ldlr expression and reduce serum cholesterol and LDL-C in hyperlipidemic hamsters (Kong et al, 2004), with similar effects observed in HepG2 cells (Abidi et al, 2006;Li et al, 2009).…”
Section: Ldlrmentioning
confidence: 78%